2011
DOI: 10.1007/s00210-011-0679-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nociceptive and anti-inflammatory activities of (−)-α-bisabolol in rodents

Abstract: (-)-α-Bisabolol is an unsaturated, optically active sesquiterpene alcohol obtained by the direct distillation of essential oil from plants such as Vanillosmopsis erythropappa and Matricaria chamomilla. (-)-α-Bisabolol has generated considerable economic interest, as it possesses a delicate floral odour and has been shown to have antiseptic and gastroprotective activities. In this study, (-)-α-bisabolol was tested in standardised rodent models by gavage administration at doses of 100 and 200 mg/kg in the models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 40 publications
3
62
0
2
Order By: Relevance
“…The abdominal constriction response induced by acetic acid is a sensitive procedure to evaluate peripheral and central acting analgesics. It has previously been reported that reduction in the amount of constriction induced by acetic acid may be associated with several drugs by acting through different mechanisms, then being considered a nonselective antinociceptive test [21] . In general, acetic acid causes pain through the release of endogenous substances such as serotonin, histamine, prostaglandins (PGs), bradykinins and substance P [2,19] .…”
Section: Discussionmentioning
confidence: 99%
“…The abdominal constriction response induced by acetic acid is a sensitive procedure to evaluate peripheral and central acting analgesics. It has previously been reported that reduction in the amount of constriction induced by acetic acid may be associated with several drugs by acting through different mechanisms, then being considered a nonselective antinociceptive test [21] . In general, acetic acid causes pain through the release of endogenous substances such as serotonin, histamine, prostaglandins (PGs), bradykinins and substance P [2,19] .…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, three terpenoids were the main constituents identified using 1 H‐nuclear magnetic resonance: α‐bisabolol, bisabolol oxide A, and guaiazulene [Ortiz et al, ]. It has been suggested that cyclooxygenase (COX) inhibition for chamomile or its constituents is a mechanism of action for their analgesic or anti‐inflammatory properties [Srivastava et al, ; Rocha et al, ; Ortiz et al, ]. COX inhibition by NSAIDs, such as diclofenac and indomethacin, induces analgesic, antipyretic, anti‐inflammatory, and gastropathic effects [Ortiz et al, ; Sostres et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, the molecule was able to significantly decrease the MPO activity in the peritoneal fluid of rats with induced peritonitis as well as in an in vitro assay of neutrophil degranulation by using phorbol-myristate-acetate. 55 MIP-2, also known as CXCL2, and KC were reported as being important chemoattractant factors to draw neutrophils to the site of inflammation. [56][57][58] Regarding the effects of α-bis on the production of proinflammatory cytokines, the free form was able to reduce the MIP-2 level only at the highest tested dose.…”
mentioning
confidence: 99%